The acute and long‐term management of food allergy: protocol for a rapid systematic review. Issue 1 (30th March 2013) - de Silva, Debra; Panesar, Sukhmeet S; Thusu, Sundeep; Rader, Tamara; Werfel, Thomas; Muraro, Antonella; Hoffmann‐Sommergruber, Karin; Roberts, Graham; Sheikh, Aziz; ,
Abstract: Background: Allergic reactions to plant and animal derived food allergens can have serious consequences for sufferers and their families. The associated social, emotional and financial costs make it a priority to understand the best ways of managing such immune‐mediated hypersensitivity responses. Conceptually, there are two main approaches to managing food allergy: those targeting immediate symptoms and those aiming to support long‐term management of the condition. The European Academy of Allergy and Clinical Immunology is developing guidelines about what constitutes an effective treatment for food allergies. As part of the guidelines development process, a systematic review is planned to examine published research about the management of food allergy in adults and children. Methods: Seven bibliographic databases were searched from their inception to September 30, 2012 for systematic reviews, randomized controlled trials, quasi‐randomized controlled trials, controlled clinical trials, controlled before‐and‐after studies and interrupted time series. Experts were consulted for additional studies. There were no language or geographic restrictions. Studies were critically appraised using the Critical Appraisal Skills Program and Cochrane EPOC Risk of Bias tools. Only studies where people had a diagnosis of food allergy or reported a history of food allergy were included. This means that many studies of conditions that may be caused by food allergy are omitted, because only research in people with an explicit diagnosis or history was eligible. Discussion: Many initiatives have been tested to treat the immediate symptoms of food allergy (acute management) and to deal with longer lasting symptoms or induce tolerability to potential allergens (long‐term management). The best management strategies for people with food allergy are likely to depend on the type of allergy, symptom manifestations and age. There is a real need to increase the amount of high quality research devoted to treatment strategies for food allergy. Food allergy can be debilitating and is affecting an increasing number of children and adults. With such little known about how to effectively manage the condition and its manifestations, this appears a priority for future research.